Enhancing Team Communication and Critical Thinking Skills Through Case-Based Learning in Social Sciences Education for PGSD UMKABA Students - Dian Kusumawati; Ade Bagus Primadoni (AL-ISHLAH: Jurnal Pendidikan, 2025)
Developing critical thinking and communication skills is essential for prospective teachers in facing the demands of 21st-century education. Case-Based Learning (CBL) provides authentic problem contexts that encourage active discussion, collaboration, and reasoning. This study examined the effect of CBL on team communication skills in the Social Science Education course for PGSD students at Universitas Muhammadiyah Kendal Batang (UMKABA). A quantitative descriptive design with a pre-test–posttest approach was used, involving 24 students selected through saturation sampling. Data were collected using questionnaires supported by observations and interviews, and analyzed using paired sample t-tests. The findings revealed a significant improvement in students’ team communication skills after CBL implementation. The average communication score increased from 66.33% (Good) in the pre-test to 81.83% (Very Good) in the posttest (t = -19.728, p 0.001). Improvements were also observed in collaboration and interaction indicators, demonstrating that CBL fostered active participation, constructive dialogue, and teamwork. These results confirm that CBL effectively enhances not only students’ cognitive engagement but also their interpersonal skills, which are critical for future teachers. The findings align with constructivist learning theory, emphasizing that meaningful knowledge is developed through collaborative and interactive processes. CBL significantly improves PGSD students’ communication, collaboration, and interaction skills in social science education. This study suggests that integrating CBL into teacher education curricula can strengthen graduates’ readiness as adaptive and communicative educators.